Immunoglobulin E-virus phenotypes of infant bronchiolitis and risk of childhood asthma - Shibata, Ryohei; Zhu, Zhaozhong; Ooka, Tadao; Freishtat, Robert J.; Mansbach, Jonathan M.; Pérez-Losada, Marcos; Ramos-Tapia, Ignacio; Teach, Stephen; Camargo, Carlos A.; Hasegawa, Kohei (Frontiers in Immunology, 2023)
Background: Bronchiolitis is the leading cause of infant hospitalization in U.S. and is associated with increased risk for childhood asthma. Immunoglobulin E (IgE) not only plays major roles in antiviral immune responses and atopic predisposition, but also offers a potential therapeutic target. Objective: We aimed to identify phenotypes of infant bronchiolitis by using total IgE (tIgE) and virus data, to determine their association with asthma development, and examine their biological characteristics. Methods: In a multicenter prospective cohort study of 1,016 infants (age <1 year) hospitalized for bronchiolitis, we applied clustering approaches to identify phenotypes by integrating tIgE and virus (respiratory syncytial virus [RSV], rhinovirus [RV]) data at hospitalization. We examined their longitudinal association with the risk of developing asthma by age 6 years and investigated their biological characteristics by integrating the upper airway mRNA and microRNA data in a subset (n=182). Results: In infants hospitalized for bronchiolitis, we identified 4 phenotypes: 1) tIgElowvirusRSV-high, 2) tIgElowvirusRSV-low/RV, 3) tIgEhighvirusRSV-high, and 4) tIgEhighvirusRSV-low/RV phenotypes. Compared to phenotype 1 infants (resembling “classic” bronchiolitis), phenotype 4 infants (tIgEhighvirusRSV-low/RV) had a significantly higher risk for developing asthma (19% vs. 43%; adjOR, 2.93; 95% CI, 1.02–8.43; P=.046). Phenotypes 3 and 4 (tIgEhigh) had depleted type I interferon and enriched antigen presentation pathways; phenotype 4 also had depleted airway epithelium structure pathways. Conclusions: In this multicenter cohort, tIgE-virus clustering identified distinct phenotypes of infant bronchiolitis with differential risks of asthma development and unique biological characteristics.